Explaining labour market inactivity in migrant-sending families: Housework, hammock, or higher education? - Dennis Görlich; Toman Omar Mahmoud; Christoph Trebesch (Kiel Institute for the World Economy (IfW), 2007)
This article presents a new perspective on the impact of migration and remittances on labour market participation and time allocation in migrant-sending families. Departing from the common finding that labour market participation is lower in migrant households, we investigate whether the reasons for inactivity, i.e. leisure consumption, home production and higher education are affected by migration. Based on household survey data from Moldova, our results challenge the assertion that those who stay behind consume more leisure. Instead, living in a migrant household implies higher probabilities of intra-household labour substitution and a substantially higher likelihood of university enrolment.
Keywords: F22; J22; O15; C35; 330; Remittances; Labour Supply; Time Allocation; Moldova; Migration; Rücküberweisung (Migranten); Migranten; Familienökonomik; Arbeitsangebot; Moldawien